Pengaruh Content Marketing dan Citra Merek UNIQLO Terhadap Keputusan Pembelian - Matthew Natanael; Devon Johannes; Surianto Surianto (Cantaka: Jurnal Ilmu Ekonomi dan Manajemen, 2026)
The high intensity of social media usage in Indonesia, which has reached 143 million active users in 2025, has encouraged global fashion companies to optimize marketing content and strengthen brand image to influence consumer purchasing decisions. However, inconsistent findings in previous studies highlight the need for further research, particularly in the context of global fashion brands in the Indonesian market. This study aims to analyze the effect of marketing content (X1) and brand image (X2) on the purchasing decisions of Uniqlo products in Indonesia (Y), both partially and simultaneously. This study employs a quantitative approach with multiple linear regression analysis. The sample consisted of 200 respondents who are consumers of Uniqlo products in Indonesia, selected through purposive sampling, with data collected via an online questionnaire. The results indicate that marketing content (X1) and brand image (X2) each have a positive and significant effect on purchasing decisions (Y) partially, as well as simultaneously. Therefore, both variables are proven to be effective strategies for Uniqlo in driving consumer purchasing decisions in Indonesia.